Female-Headed Households in Yogyakarta, Indonesia: Demographic Realities and Policy Pathways for Inclusive Development - Alfana, Muhammad Arif Fahrudin; Qonitah, Ajeng (Populasi, 2025)
This study examines the demographic profile and policy implications concerning female-headed households in the Special Region of Yogyakarta, Indonesia. Using a descriptive quantitative approach based on secondary data from the 2023 Population Administration Database, the analysis employed frequency distributions, percentage breakdowns, and simple visualizations to profile socio-demographic characteristics and spatial variations across districts. The analysis reveals that the majority of female household heads are elderly (57% aged 60 years and above), have low educational attainment (42.8% completed only primary school or less), and are engaged in informal or subsistence employment (over 67% work in unpaid domestic work, farming, or casual labor). These patterns suggest heightened socio-economic vulnerability and limited access to formal support systems. The study integrates insights from recent international literature, emphasizing the importance of psychological empowerment, adult education, and economic inclusion in improving the quality of life for female heads of households. Based on these findings, the study proposes region-specific policy recommendations focused on skill development, access to formal employment, expanded adult education, community-based psychosocial support, and inclusive social protection. This paper contributes to the growing body of literature on gender and household dynamics by offering a localized, data-driven analysis and proposing holistic policy interventions that respond to the unique socio-demographic realities of female-headed households in SPecial Region of Yogyakarta. The results aim to inform policy strategies that promote social equity and sustainable regional development.